Welcome 2016! Part 21

Algebra Level 3

5 1 × 3 + 5 2 × 4 + 5 3 × 5 + 5 4 × 6 + = A B \large \dfrac{5}{1 \times 3}+\dfrac{5}{2\times 4}+\dfrac{5}{3 \times 5}+\dfrac{5}{4\times 6}+\cdots = \dfrac{A}{B}

Given that A A and B B are coprime positive integers, find A B A-B .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Akshat Sharda
Dec 28, 2015

= n = 1 5 n ( n + 2 ) = 5 2 n = 1 ( 1 n 1 n + 2 ) = 5 2 ( n = 1 1 n n = 3 1 n ) = 5 2 ( 1 + 1 2 ) = 15 4 15 4 = 11 \begin{aligned} & = \displaystyle \sum^{\infty}_{n=1}\frac{5}{n(n+2)} \\ & = \frac{5}{2} \displaystyle \sum^{\infty}_{n=1}\left(\frac{1}{n}-\frac{1}{n+2}\right) \\ & = \frac{5}{2} \left(\displaystyle \sum^{\infty}_{n=1}\frac{1}{n}- \displaystyle \sum^{\infty}_{n=3} \frac{1}{n}\right) \\ & = \frac{5}{2}\left(1+\frac{1}{2}\right) \\ & = \frac{15}{4} \\ & \Rightarrow 15-4 = \boxed{11} \end{aligned}

How does 5/2 come out?

Abu Bakar Khan - 5 years, 5 months ago

Log in to reply

= n = 1 5 n ( n + 2 ) = 5 n = 1 1 n ( n + 2 ) = 5 n = 1 1 2 ( 1 n 1 n + 2 ) = 5 2 n = 1 ( 1 n 1 n + 2 ) = \displaystyle \sum^{\infty}_{n=1}\frac{5} {n(n+2)} \\ = 5 \displaystyle \sum^{\infty}_{n=1}\frac{1} {n(n+2)} \\ =5 \displaystyle \sum^{\infty}_{n=1}\frac{1}{2}\left(\frac{1}{n}-\frac{1}{n+2}\right) \\ = \frac{5}{2} \displaystyle \sum^{\infty}_{n=1}\left(\frac{1}{n}-\frac{1}{n+2}\right)

Akshat Sharda - 5 years, 5 months ago

Log in to reply

It makes sense now. Thanks!

Abu Bakar Khan - 5 years, 5 months ago

same way exactly

Kaustubh Miglani - 5 years, 5 months ago

should not the geometric series 1/n diverge as n tends to infinity? thanks

guido barta - 5 years, 5 months ago

Log in to reply

= ( n = 1 1 n ) ( n = 3 1 n ) = ( 1 + 1 2 + 1 3 + 1 4 + ) ( 1 3 + 1 4 + 1 5 + ) = 1 + 1 2 + ̸ 1 3 + ̸ 1 4 + ̸ 1 3 ̸ 1 4 ̸ 1 5 = 1 + 1 2 = 3 2 =\left(\displaystyle \sum^{\infty}_{n=1}\frac{1}{n}\right)-\left(\displaystyle \sum^{\infty}_{n=3} \frac{1}{n}\right) \\ =\left(1+\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\ldots\right)-\left(\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+\ldots \right) \\ = 1+\frac{1}{2}+\not{\frac{1}{3}}+\not{\frac{1}{4}}+\ldots- \not{\frac{1}{3}}-\not{\frac{1}{4}}-\not{\frac{1}{5}}-\ldots \\ =1+\frac{1}{2}=\frac{3}{2}

Akshat Sharda - 5 years, 5 months ago

Log in to reply

you are great

guido barta - 5 years, 5 months ago

Log in to reply

@Guido Barta No problem!

Akshat Sharda - 5 years, 5 months ago
Adams Ayoade
Mar 25, 2016

Woah,solved same way.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...